Nutrition and Health - Abstracts of Oral Presentations - Editor, The (Nepal Journal of Epidemiology, 2014)
Abstracts of the Oral Presentations at the session on Nutrition and Health at the International Conference on Research Methodology and Research Writing (ICRMSW) 2013. DOI: http://dx.doi.org/10.3126/nje.v4i2.10175